The nonvesicular sterol transporter Aster-C plays a minor role in whole body cholesterol balance - Banerjee, Rakhee; Hohe, Rachel C.; Cao, Shijie; Jung, Bryan M.; Horak, Anthony J.; Ramachandiran, Iyappan; Massey, William J.; Varadharajan, Venkateshwari; Zajczenko, Natalie I.; Burrows, Amy C.; Dutta, Sumita; Goudarzi, Maryam; et al. (Frontiers in physiology, 2024)
The Aster-C protein (encoded by the gene) is an endoplasmic reticulum (ER) resident protein that has been reported to transport cholesterol from the plasma membrane to the ER. Although there is a clear role for the closely-related Aster-B protein in cholesterol transport and downstream esterification in the adrenal gland, the specific role for Aster-C in cholesterol homeostasis is not well understood. Here, we have examined whole body cholesterol balance in mice globally lacking Aster-C under low or high dietary cholesterol conditions. Age-matched and mice were fed either low (0.02%, wt/wt) or high (0.2%, wt/wt) dietarycholesterol and levels of sterol-derived metabolites were assessed in the feces, liver, and plasma. Compared to wild type controls ( ) mice, mice lacking ( ) have no significant alterations in fecal, liver, or plasma cholesterol. Given the potential role for Aster C in modulating cholesterol metabolism in diverse tissues, we quantified levels of cholesterol metabolites such as bile acids, oxysterols, and steroid hormones. Compared to controls, mice had modestly reduced levels of select bile acid species and elevated cortisol levels, only under low dietary cholesterol conditions. However, the vast majority of bile acids, oxysterols, and steroid hormones were unaltered in mice. Bulk RNA sequencing in the liver showed that mice did not exhibit alterations in sterol-sensitive genes, but instead showed altered expression of genes in major urinary protein and cytochrome P450 (CYP) families only under low dietary cholesterol conditions. Collectively, these data indicate nominal effects of Aster-C on whole body cholesterol transport and metabolism under divergent dietary cholesterol conditions. These results strongly suggest that Aster-C alone is not sufficient to control whole body cholesterol balance, but can modestly impact circulating cortisol and bile acid levels when dietary cholesterol is limited.